Estimation of sea state parameters by the wave buoy analogy with comparisons to third generation spectral wave models. (15th November 2020) - Nielsen, Ulrik D.; Dietz, Jesper
Abstract: This paper presents a study focused on sea state estimation along the route of an in-service container ship. The paper is concerned with the wave buoy analogy in which wave-induced motions of the ship are processed and analysed together with corresponding motion transfer function to give the directional wave spectrum exactly at the point of operation. In this study, a simple and inexpensive instrumentation of the vessel is considered, and wave spectrum estimation is based on measurements from one motion response unit mounted close to the forward perpendicular of the ship. The estimates by the wave buoy analogy are compared with two sets of results from third generation spectral wave models, with one set provided by a commercial supplier and with another set obtained from the Copernicus Climate Change Service Information. Motion measurements from a seven-days voyage across the Pacific Ocean are studied, and it is shown that the wave buoy analogy estimates wave conditions, in terms of sea state parameters, in good agreement with the reports by the sets of ocean wave hindcasts. Along with the comparisons, the paper discusses some of the inherent drawbacks of the wave buoy analogy, notably the fact that a ship acts as a low-pass filter. Highlights: Wave spectrum estimation based on in-service motion measurements from a container ship. Estimates are obtained using a simple instrumentation (a single MRU) together with strip theory calculations. Comparisons with hindcast data from both a commercial supplier and the Copernicus Climate Change Service Information.